Freedoms in the khaki: gendering a ‘gender- neutral’ uniform - Mary Ann Chacko (Gender and Education, 2019)
Drawing on data from an ethnography of the school-based Student Police Cadet (SPC) program in Kerala, India, this paper examines the ways in which female high school student-cadets mobilized SPC’s uniform in their performance of citizenship education. Unlike their gendered school uniforms, SPC’s gender-neutral ‘khaki’ uniform signified a program that treats girls and boys ‘equally.’ Further, SPC uniform’s resemblance to the Kerala police uniform enabled female cadets to momentarily disrupt gender regimes and lay claim to specific forms of aspirational, spatial, and sartorial freedoms. These freedoms, however, are premised on the masculine authority of the police uniform and its associated protections. Thus, while the promise of female empowerment is pivotal to SPC curriculum, the conditional nature of freedom in khaki underscores the ambivalent nature of those curricular promises. The paper concludes by examining the implications of freedom bequeathed through masculine forms of protection for girls’ participation in society.